2019
DOI: 10.3390/sym11010050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH, Acid and Thermal Treatment Conditions on Co/CNT Catalyst Performance in Fischer–Tropsch Reaction

Abstract: Multiwalled carbon nanotubes (CNT) supported cobalt oxide was prepared as a catalyst by strong electrostatic adsorption (SEA) method. The CNT support was initially acid- and thermal-treated in order to functionalize the support to uptake more Co clusters. The Co/CNT were characterized by a range of analytical methods including transmission electron microscopy (TEM), temperature programmed reduction with hydrogen (H2-TPR), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Raman spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Some researchers recorded the influence of operating conditions on the product selectivity for cobalt-based catalysts [20,24,25] and revealed that the olefin selectivity of the hydrocarbon product range reduced with rising pressure, which has reported in prior studies [19,21,24]. This study is a continuation of previous research that has been examined and published [26][27][28][29][30]. The current investigation aims to prepare cobalt manganese bimetallic catalysts on CNT substrate employing SEA technique, also to study effects of temperature, syngas space velocity, and catalyst stability through Fischer-Tropsch synthesis by performing Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Some researchers recorded the influence of operating conditions on the product selectivity for cobalt-based catalysts [20,24,25] and revealed that the olefin selectivity of the hydrocarbon product range reduced with rising pressure, which has reported in prior studies [19,21,24]. This study is a continuation of previous research that has been examined and published [26][27][28][29][30]. The current investigation aims to prepare cobalt manganese bimetallic catalysts on CNT substrate employing SEA technique, also to study effects of temperature, syngas space velocity, and catalyst stability through Fischer-Tropsch synthesis by performing Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionsupporting
confidence: 70%
“…Carbon mass balance was calculated from the moles of carbon entering the reactor relative to the moles of carbonaceous products formed. The advantage and novelty of the current studies were performed by the SEA method for synthesizing Co-Mn catalysts on CNT support for Fischer-Tropsch (FT) reaction, which has not been reported previously [26][27][28][29]. A high percentage of CO conversion and C 5+ selectivity was obtained in the present investigation.…”
Section: Process Results Dissectionmentioning
confidence: 72%
“…The surface properties of carbon materials can be modified by thermal treatment which can, in turn, impact Co dispersion and reducibility. Akbarzadeh et al [126,247] reported that thermal treatment of CNT following an acid refluxing step could enhance Co dispersion and avoid sintering and deactivation of active sites during the FTS. For CNTox support, the thermal pretreatment at high temperature led to surface de-functionalization by decomposition of surface oxygen groups (-C=O, -COOH, -OH) as shown on Figure 37.…”
Section: Surface Mofication Of Carbon By Thermal Treatmentmentioning
confidence: 99%
“…From a reaction with concentrated nitric acid, the OH functional groups were found present on the surface of the CNT, which provide active sites for the attachment of the cobalt particles. Wet chemical oxidation is the most common method for functionalizing and activating the CNT [16,17]. Accordingly, 2 g of as-received CNT were charged into a single-necked, round-bottom flask with 35 vol% nitric acid.…”
Section: Purification and Functionalization Of Cnt Supportmentioning
confidence: 99%